Adaptation of intensive methods of a foreign language teaching to the conditions of a non-linguistic university - Zara Mukhamcherievna Shadzhe (Вестник Майкопского государственного технологического университета)
The relevance of the research. One of the most urgent problems of modern vocational education is the intensive development of professional competencies of future specialists.Formulation of the problem. The existing models of intensive foreign language teaching do not fully meet the current requirements of a non-linguistic university, and do not take into account the professional content of teaching a foreign language. The problem is to identify ways to adapt intensive methods to the requirements of educational standards of a non-linguistic university, to the professional content of education.The goal is to identify opportunities for the development of integrated professional and communicative competence using the means of a foreign language.The research methods used are analysis, generalization, observation, forecasting. The provisions on intensive teaching of a foreign language by G.A. Kitaygorodskaya make up the methodological basis. In the course of the research, the literature on the topic of the study has been analyzed, targeted observations made over the course of intensive classes, written works and creative projects of students studied. The obtained results have been verified in the process of experimental work at Maikop State Technological University.The results and key findings. As a result of the research, a model of intensive teaching of a foreign language in a non-linguistic university has been formed, it has been proved that teaching a professional foreign language in a non-linguistic university will be rational if the goals, methods and means of the intensive method are adapted to the professional content of education.